2018
DOI: 10.3390/ijerph15122652
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Antibiotic in Wastewater Using Liquid Nitrogen-Treated Carbon Material: Material Properties and Removal Mechanisms

Abstract: Antibiotic residues in the aquatic environment have become a global problem posing a serious threat to the environment and an inherent health risk to human beings. In this study, experiments were carried to investigate the use of carbon material modified by liquid nitrogen treatment (CM1) and carbon material unmodified by liquid nitrogen treatment (CM2) as adsorbents for the removal of the antibiotic ampicillin from aqueous solutions. The properties of the CMs (CM1 and CM2) and the effects of variations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A rather new study on the removal of ampicillin from wastewater showed a comparison between the performances of liquid nitrogen-treated (CM1) and -untreated (CM2) carbon materials. 54 The adsorption capacities of CM1 with 550.52 m 2 /g and CM2 with 422.93 m 2 /g BET surface areas were found to be 206.00 and 178.423 mg/g, respectively. In our study, the BET surface area of the CA was found as 104.2 m 2 /g, which is almost 4–5 times smaller than that of CM1 and CM2, whereas when the adsorption capacities are compared, there is only up to 2 times difference between them.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A rather new study on the removal of ampicillin from wastewater showed a comparison between the performances of liquid nitrogen-treated (CM1) and -untreated (CM2) carbon materials. 54 The adsorption capacities of CM1 with 550.52 m 2 /g and CM2 with 422.93 m 2 /g BET surface areas were found to be 206.00 and 178.423 mg/g, respectively. In our study, the BET surface area of the CA was found as 104.2 m 2 /g, which is almost 4–5 times smaller than that of CM1 and CM2, whereas when the adsorption capacities are compared, there is only up to 2 times difference between them.…”
Section: Resultsmentioning
confidence: 90%
“…A rather new study on the removal of ampicillin from wastewater showed a comparison between the performances of liquid nitrogen-treated (CM1) and -untreated (CM2) carbon materials . The adsorption capacities of CM1 with 550.52 m 2 /g and CM2 with 422.93 m 2 /g BET surface areas were found to be 206.00 and 178.423 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4 , the q e can be affected by effect of ACAF mass; so that an increase in ACAF mass (0.1 to 1.5 g/L) leads to diminish it (98.15 to 16.26 mg/g). This may be explained according to the collision of adsorbent particles with each other and the formation of bulk; this reduces the active sites for adsorption of ampicillin [ 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…89 The removal of Cd 2+ by CAC and CAC-CO 2 demonstrated negative enthalpy values (ΔH°C AC = −24.8 kJ mol −1 ; ΔH°C AC-CO2 = 16.0 kJ mol −1 ), which implies an exothermic process. 90 The positive entropy values (ΔS°) indicate the degree of process irregularity and satisfy the second law of thermodynamics, 91 with an increase in the solid-solution interface randomness, 92 as well as the adsorbent-adsorbate affinity, and dissociative adsorption reaction. 88,93,94 Thus, ΔS°> 0 could suggest the low reversibility of the adsorption reaction.…”
Section: + Adsorption Equilibriummentioning
confidence: 99%